New Horizons in the Study of Early African Christianity - Helleman, Wendy Elgersma (Vox Patrum, 2022)
Teaching early Christianity in Nigeria and elsewhere in Africa since 2002, has convinced this author how important it is for African Christians to know of the deep roots of Christianity in Africa, and recognize the important early African theologians, Tertullian, Origen, Athanasius and Augustine, just to name a few. This argument has a significant precedent among 19th century African Christians encouraged by the unbroken presence of Christianity from antiquity in Ethiopia. In the US, Thomas Oden promoted the study of pre-Islamic Christian Africa through the Centre for Early African Christianity, and publications like the series, Ancient Christian Commentary on Scripture. This Centre has also encouraged universities in Africa to get involved in deciphering archeological materials and documents from North African sites as evidence for Christianity from its earliest days; the study of such documents has recently been established at the University of Jos (Plateau State, Nigeria). These initiatives are doubly significant because Christianity is growing phenomenally throughout Africa and is often accused of being “mile wide and an inch deep”.